Amino-acid-substituted polyacetylene-based chiral core–shell microspheres: helix structure induction and application for chiral resolution and adsorption. Issue 44 (29th October 2021) - Yin, Lijie; Duan, Huimin; Chen, Tao; Qi, Dongming; Deng, Jianping
Abstract : The random coil polymer was first compounded with substrate and induced it into helical structure subsequently. Abstract : The chiral composite materials currently synthesized with helical polymers directly compounded with the substrate, due to changes in chemical bonds and steric hindrance during the compounding process, may result in destruction of the helical structure. This article reports on a novel method to prepare chiral core–shell microspheres. Specifically, a random coil polymer was first compounded with the substrate and subsequently induced into a helical structure. We have synthesized chiral core–shell microspheres using amino-acid-substituted polyacetylene and preformed polydivinylbenzene (PDVB) microspheres. It was found that the polymer chains forming the shell can transform from random coil to one-handed helix in aqueous Cu 2+ solution. Due to their outstanding optical activity, the chiral microspheres successfully induced enantioselective crystallization and adsorption from racemic Boc-(D, L )-alanine, Boc-(D, L )-asparagine, (D, L )-methionine and (D, L )-proline, with ee up to 95%, 90%, 78% and 80%. This work presents a new strategy to fabricate chiral composite materials and provides the possibility to synthesize chiral materials from nonhelical structured polymers.